Bioremediasi untuk Menurunkan Kadar Insektisida Klordan di Lahan Sawah - Indratin, Indratin; Wahyuni, Sri; Setyanto, Prihasto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Bioremediation   is   one   of the effective   ways   to   remediate   pesticide-contaminated   land,   in order to   reduce environmental pollution problems. Bacillus substillis, Heliothrix oregonensis, Catenococcus thiocycli,and Achoromobacter sp are soil microbes which are capable of lowering the levels of chlordanein the fields. These microbes derived from preliminary research results indigenous soil insulation in the Laboratory of Microbiology LIPI Cibinong. This research is aimed to determine the decrease levels of chlordane in paddy fields cultivated with rice Ciherang variety using bioremediation treatment. The soil used for the planting medium is taken from Cilamaya village, District CilamayaWetan,   Karawang.  This research   is conducted   at   Jakenan Research Station from January to December 2013. This research uses  activated carbon coated urea and biochar enriched by   indigenous  microbes with  a dose 250 kg/ha. This research is designed by using  complete   randomized   block  design  which   is   repeated   three times with for 40 ml microbial concorcia populations 109 in 1 kg of urea coated by biochar or activated carbon. The microplot size 1 x 1 m with spacing of 20 x 20 cm. Insecticide residue analyzes carried out in Balingtan Laboratory in Bogor by gas chromatography, using the SNI 06-6991.1-2004method. The result shows  biochar coconutshell-coated  urea   enriched   with  microbes   in  rice   farming   can  reduce   pesticide  residues   chlordane amountedto 27.10%